STRATEGI PENGELOLAAN ASET TETAP DI KECAMATAN KEJAKSAN KOTA CIREBON - Purwanti, Nurani Yuni; Fariyanti, Anna; Ristiyanto, Nirwan (Jurnal Manajemen Pembangunan Daerah, 2018)
ABSTRACTRegional assets are an important component of governance and public services. Management of good local assets to produce information in the preparation of financial statements must meet the completeness of the document management of local property in accordance with the regulations. The purpose of this study is to formulate the strategies for management of fixed assets in Kejaksan district. Analytical methods which were specifically implemented in order to achieve the purpose of the study are descriptive analysis, likert scale, and Analytical Hierarchy Process (AHP). Sources of data used in this study are questionnaires and interviews to 10 managers of fixed assets in in Kejaksan district and 4 expert respondents .Strategies resulting from Analytical Hierarchy Process (AHP) are: (1) technical guidance of fixed asset management, (2) guidance and control of direct supervisor, (3) application of reward and punishment, (4) periodic asset management socialization , (5) improvement of infrastructure facilities for fixed asset management, and (6) policy making on the management of new fixed assets. Keywords: Management Of Fixed Assets, Techcical Guidance, Guidance And Control, Facilities Infrastructure, Analytical Hierarchy ProcessABSTRAKAset daerah merupakan komponen penting dalam penyelenggaraan pemerintahan dan pelayanan publik. Pengelolaan aset daerah yang baik guna menghasilkan informasi dalam penyusunan laporan keuangan harus memenuhi kelengkapan dokumen pengelolaan barang milik daerah sesuai peraturan yang berlaku. Tujuan dari penelitian ini adalah untuk merumuskan strategi perbaikan dengan menggunakan Analytical Hierarchy Process. Sumber data yang digunakan dalam penelitian ini adalah kuesioner dan wawancara kepada 4 responden yang dianggap ahli. Strategi perbaikan yang dihasilkan dari Analytical Hierarchy Process (AHP) adalah: (1) pembinaan teknis pengelola aset tetap, (2) pembinaan dan pengendalian dari atasan langsung, (3) penerapan reward dan punishment, (4) sosialiasi pengelolaan aset secara berkala, (5) peningkatan sarana prasarana pengelola aset tetap, dan (6) pembuatan kebijakan mengenai pengelolaan aset tetap terbaru.Kata Kunci: Pengelolaan Aset Tetap, Pembinaan Teknis, Pembinaan Dan Pengendalian, Sarana Prasarana, Analytical Hierarchy Process